Effects of solvents on polymorphism and shape of mefenamic acid crystals - Abdul Mudalip, Siti Kholijah; Abu Bakar, Mohd Rushdi; Jamal, Parveen; Adam, Fatmawati; Che Man, Rohaida; Sulaiman, Siti Zubaidah; Mohd Arshad, Zatul Iffah; Md. Shaarani, Shalyda (EDP Sciences, 2018)
Mefenamic acid [2-(2, 3-dimethylphenyl) amino benzoic acid] is an active pharmaceutical compound that exist in different polymorphic form and shape. In this work the effect of solvents on polymorphism and shape of mefenamic acid crystals were examined. The solvents used were ethanol, isopropanol, ethyl acetate, dimethyl acetamide, dimethyl formamide, and acetone. Natural cooling was employed during the crystallisation process. The crystals produced were dried and analysed using optical microscopy, differential scanning calorimetry, thermal gravimetric analysis, x-ray powder diffraction (XRPD) and fourier transform infrared spectroscopy (FTIR). The analysis confirmed that the crystals obtained using ethyl acetate, ethanol, isopropanol, and acetone are pure Form I with a needle-like flat shape. Meanwhile, the crystallisation using DMF produced polymorphic Form II in cubic shape.